Categories of Functional Analysis - Chávez Guevara, Leonaldo (2024)
The objective of this article is to categorically focus on some aspects of Functional Analysis, aiming to present a high-level methodology for research and teaching. In section 1 the notions of category and subcategory are given; The Identification Convention and the Principle of Duality are stated; Some categories are presented and important properties of their objects and morphisms are stated. In section 2, functors and natural transformations are studied, showing their importance through examples that connect algebra and topology. In section 3 the important notions of limit of a functor and of adjunction of functors are given, and some examples are considered.